A diplomacia e os diplomatas na baixa Idade Média portuguesa (1431-1475) - Duarte Maria Monteiro de Babo Marinho (Medievalista)
Our main objective is to carry out an overall reflection on the men who formed the Portuguese royal diplomacy between 1431 and 1475. Therefore, in addition to pointing out some lines of force regarding the constituent members of the Portuguese embassies, like the composition the characteristics of diplomatic agents and the monarch's strategies for recruitment, we will seek to highlight certain issues such as the acquisition of skills and the duration of careers.